P‐Hacking, P‐Curves, and the PSM–Performance Relationship: Is There Evidential Value?. (20th October 2020) - Vogel, Dominik; Homberg, Fabian
Abstract: Recent developments in the social sciences have demonstrated that we cannot uncritically aggregate the published research on a particular effect to conclude about its presence or absence. Instead, questionable research practices such as p‐ hacking (conducting additional analyses or collecting new data to obtain significant results) and selective publication of significant results can produce a body of published research that misleads readers even if it contains many significant results. It is, therefore, necessary to assess the evidential value of the research on a certain effect; that is, one must rule out that it is the result of questionable research practices. We introduce the p‐curve method to public administration research and apply it to the research on the relationship between public service motivation (PSM) and individual performance, to demonstrate how the evidential value of a body of published research can be assessed. We find that this particular literature contains evidential value.